Impact of demonetization on Indian citizens - Soni, Shriprakash; Karande, Vinit (International research journal of management, IT and social sciences, 2017)
A paper currency i.e. currency note is basically a promissory note that simply recommends that the payee has ’promised’ to pay that amount to the payer. The same is written on every currency paper as well. This is authenticated in India by the RBI Governor. This currency notes people can you for the exchange of goods and services. It is considered as a legal tender for performing transactions. Demonetization means the ’scrapping’ of old currency notes and canceling their legal status of tender. Shri Narendra Modi, The Indian Prime Minister, in his speech to the nation on 8th November 2016 declared the demonetization of the Indian currency notes Rs. 1000 and Rs. 500 with effect midnight of 8th November 2016. This move sent the whole country in a wobbly. The Hon’ble Prime Minister specified this decision is a decisive attack against the black money being stored by the citizens of the country as well as a step to counter terrorism which was being funded by counterfeit money.